(3fUGH GdGMJSGHs - (3YeQ Hf eMeO Hf YhV GdTGej GdMfaj GdSfGej,J (B696 (3g` s ((3eUWai Hf fhQGddg s)
(3ChdgG (B:s
(3GdMeO ddg GdMHjH GdQbjH Ydi fhGdg EjeGfkG hGMJSGHkG hGdUdGI Ydi QShdg GdfSjH hBdg s
(3BNQgG (B:s
(3Je GdcJGH HYhf Gddg JYGdi Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B317s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1953s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs